Single-stage separation and quantitation of anionic and cationic forms of transition metals from environmental water using organo-functionalized ordered mesoporous silica - Natalia Kobylinska (Chemical Engineering Journal Advances)
A simple methodology was proposed for the separation and quantitation of toxic heavy metals (Pb2+, Cr3+, Cu2+, Mn2+, Cd2+, CrO42- and MnO4-) in the fixed-bed column and batch adsorption experiments using functionalised mesoporous silicas. For this reason, SBA-15 silica with covalently immobilized ethylenediaminetriacetic acid (referred to as MS/EDTA) and quaternary ammonium groups (labelled to as MS/QAS) has been successfully prepared using a post-synthesis approach. The MS/EDTA and MS/QAS samples were characterized by N2 adsorption/desorption isotherms, FTIR, XPS, SEM and TEM measurements, elemental and titrimetric analysis. Functionalized materials of the SBA-15 type was shown to have a specific surface area of approximately 715-745 m2/g. This kind of materials was applied for the adsorption process at static and dynamic conditions after corresponding optimizations with respect to pH values, amount of adsorbent, contact time, interfering compounds on the removal of target ions. All adsorbents exhibit fast adsorption rate and high adsorption capacity. Excellent maximum adsorption capacity of MS/EDTA sample was observed for Pb(II) and Cr(III) ions (until 1.55 mmol/g) at pH 6.5. The Kd values of target cations was reached up to 1.8×104 mL/g. Interfering effects caused by the presence of alkali metal ions, earth alkali metal ions and some anions were negligible. To reused of adsorbents during four-five cycles with high adsorption capacity using HNO3 solution (1 M). At the same time, the surface area and concentration (∼4 %) of functional groups on the surface of the adsorbents unchanged after four regeneration cycles. The MS/QAS sample was applied to the selective and efficient removal of Cr(VI) and Mn(VII) ions. The extraction of CrO42- ions at pH 7.5 by the MS/QAS adsorbent is practically unchanged in the presence of other divalent anions such as CO32- and SO42-. The results indicated that the adsorption capacity of the column was lower than that of the batch system. The synthesized mesoporous materials are used as effective energy-efficient adsorbents for simultaneous removal of heavy metal ions in various forms from natural water samples.